HUBUNGAN AKSES KEFASILITAS PELAYANAN, PENGETAHUAN DAN DUKUNGAN SUAMI DENGAN PEMAKAIAN KONTRASEPSI IMPLANT DI PUSKESMAS PEDAMARAN KABUPATEN OKI : Nyimas Shinta Aprilin Kesuma,Siti Aisyah, Turiyani - Nyimas Shinta Aprilin Kesuma (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2020)
A contraceptive implant is a contraceptive device which is placed under the skin, usually it is placed in the upper arm. This study aimed to find out the correlation between service facility access, knowledge and husband’s support with the contraceptive implant utilization in Pedamaran Public Health Center Year 2020. This study applied a quantitative analytical survey research design using cross sectional approach. The population of this study was taken from all mothers who become the family planning acceptors who visited Pedamaran Public Health Center. The samples of this study were 40 respondents who were taken randomly by applying accidental sampling method. The data were then analyzed using bivariate and univariate analysis. Among 40 respondents, there were 52,5 % respondents who used contraceptive implant, and 47,5 % did not use it. Based on respondents service facility access, there were 42,5 % who lived near by and 47,5 % lived far from the service facility access. There were 52,5 % respondents who had good knowledge, and 47,5 % had less knowledge. Meanwhile, there were 40, % respondents who got the support from husband, and 60 % did not. Based on the result of chi-square statistics test, service facility access variable showed that p value 0,000 (<?=0,05), it means that there was a significant corelation between service facility access with the contraceptive implant utilization. Furthermore, based on support from husband variable, it was found out that p value 0,004 (<?=0,05), it means that there was a significant corelation between support from husband with the contraceptive implant utilization in Pedamaran Public Health Center year 2020. It is advisable that Pedamaran Public Health Center be more active in giving training to midwives concerning with the contraceptive implant utilization.